A kinase profile-adapted drug combination elicits synergistic cooperative effects on leukemic cells carrying BCR-ABL1T315I in Ph+ CML. (March 2019) - Gleixner, Karoline V.; Sadovnik, Irina; Schneeweiss, Mathias; Eisenwort, Gregor; Byrgazov, Konstantin; Stefanzl, Gabriele; Berger, Daniela; Herrmann, Harald; Hadzijusufovic, Emir; Lion, Thomas; Valent, Peter
Highlights: Bosutinib synergizes with dasatinib in killing BCR-ABL1 T315I + CML cells. Synergism was confirmed in primary drug-resistant CML cells carrying BCR-ABL1 T315I . The drug combination produced cooperative effects on CD34 + /CD38 − CML stem cells. "Bosutinib + dasatinib" may be an interesting approach in TKI-resistant CML. Forthcoming studies need to clarify the value of the drug combination in vivo. Abstract: In chronic myeloid leukemia (CML), resistance against second-generation tyrosine kinase inhibitors (TKI) remains a serious clinical challenge, especially in the context of multi-resistant BCR-ABL1 mutants, such as T315I. Treatment with ponatinib may suppress most of these mutants, including T315I, but is also associated with a high risk of clinically relevant side effects. We screened for alternative treatment options employing available tyrosine kinase inhibitors (TKI) in combination. Dasatinib and bosutinib are two second-generation TKI that bind to different, albeit partially overlapping, spectra of kinase targets in CML cells. This observation prompted us to explore anti-leukemic effects of the combination dasatinib + bosutinib in highly resistant primary CML cells, various CML cell lines (K562, K562R, KU812, KCL22) and Ba/F3 cells harboring various BCR-ABL1 mutant-forms. We found that bosutinib synergizes with dasatinib in inducing growth inhibition and apoptosis in all CML cell lines and in Ba/F3 cells exhibiting BCR-ABL1 T315I . Clear synergistic effects were also observed in primary CML cells in all patients tested (n = 20), including drug-resistant cells carrying BCR-ABL1 T315I . Moreover, the drug combination produced cooperative or even synergistic apoptosis-inducing effects on CD34 + /CD38 – CML stem cells. Finally, we found that the drug combination is a potent approach to block the activity of major additional CML targets, including LYN, KIT and PDGFRα. Together, bosutinib and dasatinib synergize in producing anti-leukemic effects in drug-resistant CML cells. Whether such cooperative TKI effects also occur in vivo in patients with drug-resistant CML, remains to be determined in forthcoming studies.